How young white Afrikaans women who serve on residence student leadership at Stellenbosch University conceptualise race, racism and white privilege - Mouton, Antoinette (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2025.